MEMBANGUN RAPPORT DAN PENDEKATAN ITOP DALAM MENGURANGI TINDAKKEKERASAN DI SEKOLAH (Pada Orang Tua Peserta Didik TK Kanisius Immakulata Jagalan) - Lydia Ersta Kusumaningtyas; A. Roedy Koesdyantho; Rustika Damarwati (Adi Widya : Jurnal Pengabdian Masyarakat, 2021)
Building a report card and ITOP Approach in reducing violence in schools. This title was born because of the problems of Kanisius Immaculate Kindergarten students about an increase in violence that occurred in schools. As for the source of the problem is the relatively large number of students per class and only 1 teacher is taught and also the age of kindergarten children who are relatively small and still at the stage / period of imitation. That The target of this service is the parents of Kanisius Immaculate Kindergarten students, who are their favorite schools. This school has 90 students, so it requires more attention and is prone to violence. This service was carried out first by means of counseling then continued with training on building rapport and the ITOP approach. However, because this service was carried out during a pandemic, only 54 of the 90 parents attended (60%). After counseling and training on building rapport and the ITOP approach in reducing violence in schools there were 51 people (94.45%) of 54 people who mastered both counseling and training materials, while 3 (5.55%) did not master the training because not serious about doing training. So it can be concluded that this dedication was successfully seen from: 1. Based on the attendance of the participants it is said to be successful because it is attended by 60% 2. Based on the mastery of the participants it can be said to be successful because there are 94.45% masters 3. Those who do not understand are relatively small, namely only 5.55%